Validação do World Health Organization Disability Assessment Schedule (WHODAS 2.0) para pessoas com obesidade mórbida - BORGES, Kátia Ariana (2017)
Morbid obesity is presented in literature as a chronic non-transmissible disease that can affect every biopsychosocial aspect of an individual. Considering the Brazilian reality, scarce are the studies capable of measuring the level of functionality and deficiency of the population affected by it. Thus, this study aimed primarily at validating the World Health Organization Disability Assessment Schedule (WHODAS 2.0) to assess the functionality of people with morbid obesity. Its secondary objectives are the analysis of the quality of life of morbidly obese people and the physical and functional abilities they present, as well as the identification of their self-attributed and perceived occupational roles, as well as the importance the investigated people give to them. This study is of a methodological nature, though, to answer its secondary objectives, it was also based on a quantitative and descriptive research that had an exploratory and cross-sectional approach. In order to collect the data, the 36 item version of the WHODAS 2.0, the Short Quality of Life Scoring (WHOQOL – BREF), as well as the Six Minute Walk Test (6MWT) and the List for the Identification of Occupational Roles (LIOR) were used. Sociodemographic and clinical data were collected through an initial interview elaborated by the researchers. In total, 60 adults participated in this study, all with a Body Mass Index (BMI) of over 40kg/m² and registered in the digestive tract surgery ward of the general hospital of a public university in the Triângulo Mineiro, Minas Gerais. The results obtained through psychometric tests conducted in the first evaluation have shown a total internal consistency of 0.93, verified through the Cronbach’s alpha coefficient. The re-test test and the inter-evaluators have presented good and excellent reliability with the results of the intraclass Correlation Coefficient, varying from 0.67 and 0.95. Regarding the validity of a converging and diverging criteria, a moderate and significant correlation has been noted with most of the WHOQOL – BREF domains, together with a diverging relation between the WHODAS 2.0 and the 6MWT, and a strong correlation between the domains School Activities and WHODAS 2.0 work, and the role of the LIOR worker. Considering their quality of life, data have shown significant damages in all domains, especially in the physical one, while physical and functional capacity were shown to be diminished. Losses of occupational roles considered to be important by the sample were also found. The study showed that the WHODAS 2.0 presents meaningful psychometric properties, adequate for the use in people who are morbidly obese. It is also necessary to highlight the importance of other studies, able to find deeper connections betweenfunctionality, quality of life, physical and functional capacity, and the occupational roles of morbidly obese people.